Pengaruh Pengendalian Internal Terhadap Efektivitas Pencegahan Kecurangan Laporan Keuangan - Mariana, Syafira; Ismayanti, Rima (Journal of Business and Economics Research (JBE), 2025)
The government’s financial report serves as a form of transparent accountability in the management of state finances. However, in practice, various issues still arise, as revealed through audit results conducted by the Inspectorate, which acts as the Government Internal Supervisory Apparatus (APIP). Therefore, internal control plays a crucial role in minimizing the risk of fraud. This study aims to examine the extent to which internal control influences the effectiveness of fraud prevention. The research uses a quantitative approach through a survey method. It was conducted at the Majalengka Regency Inspectorate using a saturated sampling technique, where questionnaires were distributed to 32 Auditors and PPUPD officers as respondents. Analysis of data using normality test, linearity test, and simple regression analysis., t-test for hypothesis testing, and coefficient of determination (R²), all processed using IBM SPSS Version 25. The t-test (partial) results showed a t-count of 5.741, while the t-table value at a 0.05 significance level was 2.042. Since t-count > t-table (5.741 > 2.042), the hypothesis is accepted. This indicates that internal control significantly affects the effectiveness of fraud prevention at the Majalengka Regency Inspectorate. The coefficient of determination (R²) was 0.651, meaning that 65.1% of fraud prevention effectiveness is influenced by internal control. The remaining 34.9% is affected by other factors not examined in this research, such as auditor competence, human resource quality, external pressures, and anti-fraud policies.